Selective surface modification of lithographic silicon oxide nanostructures by organofunctional silanes - Baumgärtel, Thomas; von Borczyskowski, Christian; Graaf, Harald (Beilstein Journal of Nanotechnology, 2013)
This study investigates the controlled chemical functionalization of silicon oxide nanostructures prepared by AFM-anodization lithography of alkyl-terminated silicon. Different conditions for the growth of covalently bound mono-, multi- or submonolayers of distinctively functional silane molecules on nanostructures have been identified by AFM-height investigations. Routes for the preparation of methyl- or amino-terminated structures or silicon surfaces are presented and discussed. The formation of silane monolayers on nanoscopic silicon oxide nanostructures was found to be much more sensitive towards ambient humidity than, e.g., the silanization of larger OH-terminated silica surfaces. Amino-functionalized nanostructures have been successfully modified by the covalent binding of functional fluorescein dye molecules. Upon excitation, the dye-functionalized structures show only weak fluorescence, which may be an indication of a relatively low surface coverage of the dye molecules on length scale that is not accessible by standard AFM measurements.
Keywords: AFM lithography; amino-functionalization; local anodic oxidation; octadecyl-trichlorosilane; silicon oxide nanostructures